Tingkat Pengetahuan dan Kategori Persepsi Masyarakat Terhadap Penyakit Tuberkulosis (TB) di Desa Kecicang Islam Kecamatan Bebandem Karangasem-Bali - Luh Made Hannisa Sandha; Komang Ayu Kartika Sari (Universitas Udayana, 2017)
Knowledge and perception are very important in disease control and management of tuberculosis. A good awareness of tuberculosis will help the prevention and management program of TB to be successful. The aim of the study was to explore the level of knowledge and category of perception of the society regarding TB in Kecicang Islam village, Bebandem district, Karangasem. This research was a cross-sectional study, where the samples were from all family registers in Kecicang Islam village, Bebandem district. The instrument used was questionnaire consisted of knowledge of TB and perception of early detection of TB. Data analysis was by univariate analysis and cross tabulation. The result showed that 55.1% of the respondents had low knowledge of TB, while 67.3% had positive perception regarding early detection of TB. From this study, it could be concluded that the society of Kecicang Islam village has low knowledge and good perception of TB. Keywords: tuberculosis, knowledge, perception